Konstruksi Sosial Pengalaman Ibu Rumah Tangga dalam Pengambilan Keputusan Pinjaman Online di Desa Tarumajaya - Nugraha K., R. Arif; Charviandi, Adrie; Suhartini, Yesi; Sandya, Deasy; Noristaman, Rizka; Yusnaini, Yusnaini; Asmari, Andri; Iskandar, Diki; Ridwan, Acep; Kurniasih, Azhari Gusti; Rustiana, Candra (Universitas Prof. Dr. Moestopo (Beragama), 2026)
The proliferation of illegal online lending platforms has heightened financial vulnerability among rural housewives, who often manage household finances with limited literacy and under social pressures. This community service program aimed to empower housewives in Tarumajaya Village, Bandung, by enhancing their financial literacy and critical awareness of digital loan risks. Employing a participatory andragogy approach, the intervention integrated structured counseling, hands-on budgeting workshops, focused group discussions, and individualized consultations. Quantitative and qualitative evaluations revealed a substantial increase in participants' cognitive knowledge, with average test scores rising from 45% to 82%. Moreover, 90% of participants acquired practical skills in family budget planning and debt simulation analysis. The initiative successfully fostered a supportive peer-learning community and provided actionable solutions for individuals entangled in problematic debt. The findings underscore the efficacy of a multidimensional, community-based educational strategy in promoting prudent financial decision-making and building resilience against predatory lending practices. Sustainable impact necessitates ongoing mentorship, institutional reinforcement of village-level financial support groups, and stronger collaboration with local authorities and formal financial institutions.